Phishing Attacks Prevention and Detection Techniques - Ritika Arora, Sharad, Sanjeet Singh, Narendra Kumar, A. K. Saini (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Phishing attacks are online security attack which involves obtaining sensitive information. The attacker creates the precise copy of the prevailing web content to fool users so on hack their personal financial data, online banking passwords, ATM Card number. Phishing is becoming more hostile day by day and its detection is incredibly important. Phishers choose those websites which are visually and semantically just like those real websites. It affects diverse field like e-commerce, digital marketing by sending spam emails and develop identical websites which resembles original one. As a prevention method we are able to examine the properties like data set, feature extraction and detection algorithms, performance evaluation metrics using detection techniques. The main aim of our study is to propose a safer framework for detecting phishing websites with high accuracy in less time. This paper focuses on a comparative study and analysis of varied phishing detection mechanisms and several other countermeasures to beat them.